Inclusion of 8% alfalfa silage advances feeding time and improves late-finishing feed efficiency in pigs - Yu Chen; Xiaogang Zhao; Xionggui Hu; Ji Zhu; Huibo Ren; Huali Li; Lihua Cao; Qingming Cui; Yuan Deng; Zhicai Li; Zhongshan Wei; Weimin Jiang; et al. (PLoS ONE, 2026)
Feed is the largest cost in pig production, driving interest in alternative ingredients that maintain performance at lower expense. Alfalfa, a nutrient-rich and widely available forage legume, shows promise as a partial feed substitute. However, it remains unclear how partial replacement with alfalfa affects growth dynamics, feed efficiency, and feeding behavior across fattening stages in pigs. This study investigated the effects of substitution with 8% alfalfa or alfalfa silage on growth performance and feeding behavior in growing-finishing pigs over a 60-day fattening period (60–130 kg). A total of 24 pigs were randomly assigned to three diet treatments: commercial feed, 8% alfalfa substitution, or 8% alfalfa silage substitution. Weight, feed intake, feed conversion ratio (FCR), and feeding hour were measured and analyzed using linear mixed-effects models and generalized additive mixed models. Results showed no significant effects of alfalfa on overall weight, feed intake or FCR. However, Pigs fed commercial feed showed superior FCR during mid-fattening (weeks 2.8–5.2, P < 0.05) but worse FCR than alfalfa-fed groups during late-finishing phase (weeks 6.6–8, P < 0.05). Moreover, alfalfa silage altered animal behavior by shifting feeding hour by roughly three hours earlier (P < 0.05). In summary, substitution with 8% alfalfa or alfalfa silage can be incorporated without compromising overall pig performance. While, integrating alfalfa in later fattening stages could further improve feed efficiency and reduce costs. This supports the use of phase-specific feeding strategies and adoption of such practices could enhance both economic and environmental sustainability in commercial pig farming.